Preparation and Evaluation of Buccal Mucoadhesive Tablets of Antihypertensive Drug - Shrivastava, Aman; Rajput , Dharmendra Singh; Kushwaha, Devendra (Asian Journal of Pharmaceutical Research and Development, 2025)
Buccal route of drug delivery has significant attention to the systemic circulation through the jugular vein bypassing the first pass hepatic metabolism leading to high bioavailability. Such routes have expanded important notice due to their presystemic metabolism or instability in the acidic environment associated with the oral administration. Along with the variety of buccal layer mucosae of the oral cavity has convenient and easily effective site for the delivery of therapeutic agents. Lercanidipine a suitable candidate for buccal delivery. Hence, in this research work an attempt was made to formulate buccal tablets of Lercanidipine hydrochloride to increase patient compliance by reducing dosing frequency and to achieve plasma concentration profile over 12 h.